임신부의 건강식생활 가이드를 위한 애플리케이션 개발 소비자요구도 조사 - 김숙배(Sook Bae Kim); 김정원(Jeong Weon Kim); 김미현(Mi Hyun Kim); 조영숙(Young Sook Cho); 김세나(Se Na Kim); 임희숙(Hee Sook Lim); 김순경(Soon Kyung Kim) (Korean journal of community nutrition, 2013)
This study was conducted to assess needs of educational mobile application (App) development for nutritional management and information on pregnant women. A total of 105 pregnant women were investigated on general characteristics, dietary habits, health behavior and needs for contents and composition of the application. The mean age of the subjects was 31.9 years and the mean gestation period was 25.4 weeks. The rate of skipping meal was 39.0% and the rate of irregular meal time was 46.6%. The consciousness of the meal as balanced nutrition and health was 19.9%. Eating out at least forth a week was 35.3%. Obtaining information about pregnancy and childbirth were internet (35.3%), hospital or health center (19.9%), books (17.1%), experience (15.2%), mobile (8.6%) and friends or acquaintances (4.8%). If the application is developed, subject replied 'frequently use' (51.4%), 'when needed' (47.6%) respectively. The favour topic in developing application were 'nutrition information of pregnant and fetal' (36.2%), 'weight management, feeding' (33.3%), 'food choice and cooking' (21.9%), 'shopping' (5.7%), 'example of menu' (1.9%), 'effect of smoking, drinking, exercising' (1.0%). The favorite content was 'include sufficient amount about information' (44.8%). Depending on the age and education level, the best age for pregnancy group have significantly higher ability for utilize and information gathering than old age pregnant group. Also the best age for pregnancy group have high demands of design, convenience and various contents in App development. Therefore, mobile application (App) for pregnant women could be widely used as an effective dietary guide.